Recursivity and Self-Referentiality of Economic Theories and Their Implications for Bounded Rational Actors - Marco Lehmann-Waffenschmidt; Serena Sandri (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2007)
This study aims at the analysis of the possible self-referential effects of economic theories and models on its own subject and of the mechanisms through which bounded rational actors perceive the self-referential nature of economic theories and might absorb their prescriptions. Thus, the focus of the present study will be on the effects of economic theories on the behaviour of the analyzed economic actors. The analysis of the possible causal role of theories on bounded rational economic behaviour will be interpreted as a sort of validity test of economic theory.
Keywords: D7; D01; 330; self-referentiality; recursivity; self-altering predictions; theory absorption; bounded rationality; Wirtschaftstheorie; Wirtschaftsmodell; Wissenschaftliche Methode; Beschränkte Rationalität; Theorie